Synthesis of novel ionic liquids and evaluation of their leaching performance in the recovery of copper and zinc from industrial brass slag - Sahin, Ayfer Kilicarslan; Atalay, Tugba Selcen; Atbakar, Muge; Ocal, Nuket; Saridede, Muhlis Nezihi (CONSEJO SUPERIOR INVESTIGACIONES CIENTIFICAS-CSIC, 2016)
Imidazolium-based ionic liquids, 1,3-dibenzylimidazolium trifluoroacetate, 1-benzyl-3-ethylimidazolium trifluoroacetate and 1-benzyl-3-propylimidazolium trifluoroacetate were prepared by simple methods, when compared with those in literature sources, and characterized by IR, NMR and GC-MS and LC-MS. These ILs (Ionic Liquids) were employed as leaching agents in the treatment of industrial copper and zinc bearing slag for the recovery of metals. Results showed that synthesized all novel ionic liquids meet the standard specifications of an ionic liquid. Metal recovery rates decrease with time except for zinc dissolution in 1,3-dibenzylimidazolium trifluoroacetate. 1,3-dibenzylimidazolium trifluoroacetate, when compared with others, is a more effective leaching agent for the treatment of copper and zinc bearing brass slag. Metal recovery rates achieved with this IL are 62.58% for zinc and 24.95% for copper.
Keywords: Copper; Ionic liquid; Leach; Recovery; Synthesis; Zinc; Metallurgy & Metallurgical Engineering